2021
DOI: 10.1210/jendso/bvab048.1154
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Nephrogenic Diabetes Insipidus From Tenofovir

Abstract: Introduction: Diabetes insipidus (DI) is a clinical condition which manifests as excessive urine output, either because of impaired or inadequate antidiuretic hormone (ADH) secretion, or an inability of the kidneys to respond to ADH. Nephrogenic DI is more often drug induced. Recent clinical reports have shown that medications like tenofovir may result in nephrogenic DI as well. Tenofovir is a well-known nucleoside reverse transcriptase inhibitor analog of adenosine used in the management of both human immunod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Several studies have shown that TDF is associated with either AKI or chronic kidney disease through proximal tubal injury, either tubular necrosis or interstitial nephritis. 3,5,6,15 Indeed, our patient had pyuria with white blood cell casts suggestive of interstitial nephritis. Our case illustrates a component of tenofovir-induced Fanconi syndrome evidenced by the non-anion gap metabolic acidosis, normoglycemic glucosuria, proteinuria, hypokalaemia, hypophosphatemia, and a urine pH of 5.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Several studies have shown that TDF is associated with either AKI or chronic kidney disease through proximal tubal injury, either tubular necrosis or interstitial nephritis. 3,5,6,15 Indeed, our patient had pyuria with white blood cell casts suggestive of interstitial nephritis. Our case illustrates a component of tenofovir-induced Fanconi syndrome evidenced by the non-anion gap metabolic acidosis, normoglycemic glucosuria, proteinuria, hypokalaemia, hypophosphatemia, and a urine pH of 5.…”
Section: Discussionmentioning
confidence: 64%
“…15 Although rare, a few reports have suggested tenofovir can cause nephrogenic diabetes insipidus. [3][4][5][6][7] The cases reviewed make it clear that discontinuation of the drug is paramount and usually leads to overall improvement in all aspects of renal function. [3][4][5][6][7][10][11][12] Although our patient's baseline renal function wasn't recorded, it can be assumed that her renal impairment was attributed to the effects of tenofovir as it improved substantially after the treatment was discontinued.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations